Spiritual Well-Being as a Mediator of the Relation between Culture-Specific Coping and Quality of Life in a Community Sample of African Americans - Utsey, Shawn O. (Journal of cross-cultural psychology, 2007)
This study examines the antecedent factors affecting the quality of life of African Americans. A theoretical model is proposed that identifies the effects of culture-specific coping and spiritual well-being as predictors of quality of life. A sample of 281 African Americans was administered a battery of questionnaires that examined the constructs of interest. The theoretical model was tested within a structural equation—modeling framework to identify both direct and indirect effects. Results indicate overall model fit, with both culture-specific coping and spiritual well-being as significant predictors of quality of life. Spiritual well-being partially mediated the effects of culture-specific coping on quality of life. The article concludes with a discussion of the study's findings in relation to quality of life issues for African Americans.